Outcomes and predictors of brace treatment for girls with adolescent idiopathic scoliosis - Sun, Xu (Orthop Surg, 2010)
Objective:  To evaluate the effectiveness and to identify the predictive factors of standardized brace treatment for girls with adolescent idiopathic scoliosis (AIS). Methods:  From July 2003 to July 2009, 142 girls with AIS completed standardized brace treatment. These patients had a mean age of (13.1 ± 1.5) years (range, 10.1–15.9 years), a mean main curve of 29.6°± 5.4° (range, 20°–40°), and a mean Risser grade of 2.0 ± 1.5 (range, 0–4) before brace treatment. Based on whether their scoliosis progressed or not, patients were divided into two groups: progressed (Group Pr, n = 27, 19%) and non‐progressed (Group NP, n = 115, 81%), and were then divided into a further two groups: surgery (Group Su, n = 18, 13%) and non‐surgery (Group NS, n = 124, 87%). χ(2) and logistic regression analyses were performed to investigate factors predicting outcomes of brace treatment. Results:  The duration of brace treatment in all patients averaged 2.5 ± 1.0 years (range, 0.6–5.9). χ(2) analysis revealed that patients with progressive curves tended to be younger, with lower Risser grade, initial larger curve magnitude and a main thoracic curve pattern. Using stepwise logistic regression, pre‐menarche status (P= 0.00028) and a main thoracic curve pattern (P= 0.012) were found to be independent risk factors of curve progression despite brace treatment, while an initial Cobb angle >30° (P= 0.022) was an additional independent risk factor of curve requiring surgery due to progression. Conclusion:  Brace treatment can prevent curve progression in most girls with AIS. The outcomes of brace treatment in these girls are influenced by growth status, curve pattern and curve magnitude. Less mature patients, and those with larger curves and thoracic curves are at risk of scoliosis progression despite brace treatment.